Knowledge and perception of the Nigeria wildlife conservation laws among hunters in Lagelu and Egbeda local government areas, Oyo state, Nigeria (2021)
This study assessed the knowledge and perception of wildlife conservation laws among hunters in Egbeda and Lagelu Local Government Areas of Ibadan, Oyo state, Nigeria. The result shows that all the hunters (100%) were male, with a mean age of 50.1±13.8 years. The art of hunting was learnt by majority (84.5%) of the hunters as a form of apprenticeship from an experienced hunter or from the hunter’s father. Hunting was done on a daily basis primarily for household consumption of bushmeat, and secondarily for income generating purpose. While, majority (58.5%) claimed to have heard of wildlife conservation laws, they do not understand the meaning and significance of the laws. None of the hunters could state the number of wildlife laws that exist in Nigeria but noted that the laws hold in protected areas. On the other hand, most of the respondents (66.3%) noted that there are traditional laws (taboos) that enable wildlife conservation, especially as regards pregnant, nursing and young animals. Conclusively, hunters in the study area, despite having heard of wildlife conservation laws had a low understanding of the significance and scope of the laws. There is, therefore, a need for vigorous awareness campaign among the hunters for effective wildlife conservation.